Impact of phosphorus reduction combined with biofertilizer application on soil nutrients and microbial communities in arid oasis agricultural areas - Zhang, Yong Ling; Xiao, Rang; Zhao, Yun Chen; Li, Tongfen; Cheng, Hong Yu; Zhang, Hong Juan (Frontiers in Microbiology, 2025)
IntroductionPhosphorus reduction in agriculture is crucial for sustainable soil management, yet its interactive effects with microbial fertilizers on soil nutrient dynamics and microbial communities remain poorly understood.MethodsHere, we evaluated the impacts of phosphorus reduction at four levels [0% (P100), 15% (P85), 30% (P70), and 100% (P0)] combined with two biofertilizers—Bacillus subtilis (BF1) and Bacillus mucilaginosus (BF2)—on soil available nutrients and bacterial community structure.ResultsOur results demonstrated that P85 combined with BF1 significantly enhanced soil microbial diversity, while P85 combined with BF2 notably increased the levels of available phosphorus and potassium, without significant changes in microbial diversity but with a more pronounced shift in community structure. Microbial community analysis revealed that under BF1 treatment, the proportion of Pseudomonadota, which dominates the carbon cycle, significantly increased. Meanwhile, BF2 treatment promoted the enrichment of Acidobacteriota and Planctomycetota, both involved in carbon and nitrogen cycles. Additionally, both biofertilizers significantly increased the abundance of aerobic and biofilm-forming bacteria. Redundancy analysis (RDA) showed that nitrogen cycle-related microbiota under BF1 treatment were the primary drivers of soil nutrient changes, whereas under BF2 treatment, Acidobacteriota, Chloroflexota, and Actinomycetota (involved in carbonnitrogen cycling and organic matter degradation) contributed more to nutrient enhancement. In conclusion, the application of two biofertilizers with P85 can optimize soil nutrient availability and regulate microbial community structure, with BF1 being more beneficial for maintaining microbial diversity and BF2 having a superior effect on enhancing available phosphorus and potassium.ConclusionThe combined application of biofertilizers with phosphorus reduction demonstrates potential for improving soil health, thereby providing a scientific basis for promoting sustainable agricultural development.